Effects of CAPAH, memantine, and rivastigmine on behavioral and cognitive functions of rats - D. O. Nikitin; I. I. Semina; A. V. Valeeva; A. V. Nikitina; A. Z. Khafizova; A. G. Ovchinnikova (Фармакокинетика и Фармакодинамика)
Relevance. Alzheimer’s disease (AD) is a neurodegenerative disease characterized by cognitive and behavioral disorders. The drugs currently used in clinical practice can slow drug development but are usually associated with lifelong use because of the complexity of pathogenesis. Therefore, to correct AD, a similar approach is needed, which can be CAPAH (2-chloroethoxy-para-N-dimethylaminophenylphosphorylacetohydrazide), a potential drug with a multitarget mechanism of action.Objective. Investigate the effects of CAPAH, memantine, and rivastigmine on the behavior and cognitive functions of rats.Materials and methods. This study identified CAPAH as a potential drug with a multitarget mechanism of action. The comparator drugs were memantine (10 mg/kg) and rivastigmine (2 mg/kg). Animals were divided into 4 groups (control, CAPAH, memantine, rivastigmine), 8 males and 9 females each receiving subcutaneous injections of the respective agents for 30 days. Subsequently, their cognitive functions and behavior were studied on the «Morris Water Maze» (MWM) and «Extrapolation deliverance» (EPI) ("Open Science", Russia) with the help of the "EthovisionXT" program (Noldus, the Netherlands). Statistical processing was performed using one-way ANOVA in the GraphPadPrism 8.0.1 program.Results. In case “MWM” CAPAH increased the swimming time in the platform zone by 1.8 and 1.5 times (p < 0.05) compared with the control in the male and female groups, respectively, exceeding the parameters of the comparison drug. In case "EPI" test, the administration of CAPAH to males reduced the number of jumps by 4.4 times (p < 0.05) and increased the latent period of motor activity by 2.3 times (p < 0.05) compared with the control group, but did not affect these aspects in females.Conclusion. Administration of CAPAH improves cognitive function and memory in healthy male and female rats and reduces anxiety in male rats, whereas it outperforms the effects of memantine and rivastigmine.